2016
DOI: 10.33225/pmc/16.11.08
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control in Georgian Teachers and Its Relation to Teacher Burnout

Abstract: The intensive reforms taking place in general education field in Georgia impose considerable stress to those engaged in teaching profession. This may gradually lead to the condition of professional burnout of teachers. According to the conducted research some teachers have experienced burnout while others did not. The purpose of the present research is to identify how the personal quality such as control of locus may have influenced the level of burnout in Georgian teachers. Two self-assessment instruments, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In several studies, internal locus of control has a minor vulnerability to burnout, increasing employee commitment to the organization and professional effectiveness (Bitsadze and Japaridze, 2016). Previous research has also shown that locus of control and burnout have a significant relationship (Amir and Arshad, 2021).…”
Section: Locus Of Control and Burnoutmentioning
confidence: 98%
“…In several studies, internal locus of control has a minor vulnerability to burnout, increasing employee commitment to the organization and professional effectiveness (Bitsadze and Japaridze, 2016). Previous research has also shown that locus of control and burnout have a significant relationship (Amir and Arshad, 2021).…”
Section: Locus Of Control and Burnoutmentioning
confidence: 98%
“…However, the presence of these correlates with high resilience (Buragohain & Hazarika, 2015) which helps individuals to cope with barriers, uncertainty and negative situations (Kutluturkan et al, 2016). Similarly, teachers with internal locus of control (Rotter, 1966) have been found to be less susceptible to burnout (Bitsadze & Japaridze, 2016; Pavalache‐Ilie & Ursu, 2016). Many employees view work‐related stressors as being outside of their control which leads to traditional burnout interventions being ineffective for work‐related burnout (Kristensen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, teacher locus of control is teachers' perceptions of their personal control over and responsibility for their students' academic and behavioral outcomes (Rose & Medway, 1981). Evolved from Rotter's locus of control concept, TLOC has provided the literature with important implications regarding various notions which include but are not limited to motivation (Anderson, Hattie, & Hamilton, 2005;Czubaj, 1996), job satisfaction (Cheng, 1994), self-efficacy (Gaziel, 2008), self-regulation (Toussi & Ghanizadeh, 2012), burnout (Bitsadze & Japaridze, 2016), and student achievement (Findley & Cooper, 1983).…”
Section: Introductionmentioning
confidence: 99%